Characteristics of fluid potential and the division of hydrocarbon migration and accumulation units in the Nangong Sag, Bohai Bay Basin, China. (17th December 2022) - Liu, Tianshun; Ding, Wenlong; Yu, Zhanwen; Li, Jingtian; Wang, Sicheng; Zhou, Xu; Cheng, Xiaoyun
Abstract: The oil-gas display of early drilling suggests a considerable exploration prospect in the Nangong Sag. Previous researchers have not analyzed the characteristics of hydrocarbon migration and accumulation from the perspective of fluid potential. We use the Hubbert flow potential model to restore the flow potential of the Nangong Sag in the Pliocene, which was a key period of hydrocarbon generation. The results show that the high value area of fluid potential is large and mainly located in the southeastern part of the study area. The southeast subsag provided fluid, and the northwest slope accumulated fluid. The fluid potential gradual decrease from the southeast subsag to the northwest slope. According to the division trough theory, the Nangong Sag is divided into 8 hydrocarbon migration and accumulation units. We suggest that migration and accumulation units III, IV and V are favorable areas for hydrocarbon exploration. The study area has favorable source-reservoir-cap, pool-forming conditions and good time allocation relationship of hydrocarbon. Based on the characteristics of fluid potential, the hydrocarbon generation and accumulation modes of migration and accumulation unit III and IV in Nangong Sag are preliminarily put forward. The research results have guiding significance for future hydrocarbon exploration in the study area.